The Effect of Organizational Culture, Leadership Style, and Trust to Organizational Commitments of LP3I Polytechnic Jakarta Lectures - Dingot Hamonangan Ismail; Moch. Asmawi; Suparno Eko Widodo (Program Studi S3 Ilmu Manajemen, 2020)
The purpose of this study is to obtain valid and reliable empirical data, facts and information about the influence of organizational culture, leadership style, and trust to the organizational commitment of the LP3I Polytechnic Lecturers in Jakarta. This study makes the use of associative quantitative approach and path analysis technique. The population in this study were all permanent lecturers at the LP3I Polytechnic Jakarta with 215 people in total. The sampling method was using simple random sampling upon all permanent lecturers at the LP3I Polytechnic Jakarta who were actively working in 2017. The sample was taken using the Slovin formula and the sample size therefore was 145 lecturers. The research data was filtered through questionnaires. The results of the study concluded that there was a positive direct effect of Organizational Culture to the Organizational Commitment, there was a positive direct effect of Leadership Style to Organizational Commitment, there was a positive direct influence Trust to Organizational Commitment, there was a positive direct influence Organizational Culture to Trust, there was a positive direct influence Leadership Style to Trust , there was a positive influence of Organizational Culture, Leadership Style and trust simultaneously to Organizational Commitment and there was a positive influence of Organizational Culture and Leadership Style simultaneously to the trustworthiness of the LP3I Polytechnic Lecturers in Jakarta. This finding implied that, should you want to increase the Commitment of LP3I Polytechnic Jakarta Lecturers to the organization, it can be done through the increase of Organizational Culture, Leadership and Trust Style in a systematic and planned manner.